1974
DOI: 10.1097/00000658-197409000-00005
|View full text |Cite
|
Sign up to set email alerts
|

A Simplified Technique for Hepatic Resection

Abstract: A new technique of hepatic lobectomy with combined use of hepatic clamp and liver crush clamp is described. It is a simplification of the original finger fracture technique by using instruments instead of fingers for hepatic resection. It provides the unexperienced with a technique of hepatic resection done in the shortest possible time and in an almost bloodless field with safety. Since February 1973 the author has performed 5 hepatic resections with this crush method for primary liver cell carcinoma. The blo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
74
0
2

Year Published

1977
1977
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 123 publications
(80 citation statements)
references
References 1 publication
1
74
0
2
Order By: Relevance
“…A number of surgical devices and techniques for liver resection have been developed in order to reduce the intraoperative blood loss [8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23]. It has been reported that the amount of intraoperative blood loss was associated with the incidence of surgical complications [24,25], and perioperative blood transfusion have been shown to increase the recurrence rate of liver malignancies after surgical treatment [26].…”
Section: Introductionmentioning
confidence: 99%
“…A number of surgical devices and techniques for liver resection have been developed in order to reduce the intraoperative blood loss [8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23]. It has been reported that the amount of intraoperative blood loss was associated with the incidence of surgical complications [24,25], and perioperative blood transfusion have been shown to increase the recurrence rate of liver malignancies after surgical treatment [26].…”
Section: Introductionmentioning
confidence: 99%
“…The problem of significant blood loss during the liver parenchymal transection phase of the procedure, however, limited further advances. The ‘clamp crush’ technique, allowing controlled division of liver parenchyma, was subsequently reported in the 1970s [2]. This method enabled surgeons to ligate blood vessels and bile ducts during parenchymal transection in a controlled fashion, with or without vascular inflow occlusion (Pringle manoeuvre).…”
Section: Introductionmentioning
confidence: 99%
“…Advances in technology have elaborated the techniques for parenchymal transection during hepatectomy from the classic clamp crushing technique [18] to a combination of various sophisticated devices [19,20,21]. …”
Section: Discussionmentioning
confidence: 99%